Photoresponsive magnetic composite particles and a method for preparing the same
Patent Information
- Application Number
- CN202611344802.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-01
- Publication Date
- 2026-10-20
AI Technical Summary
[0005]另有一类以有机高分子为壳层的磁性吸附树脂材料,采用高分子包覆结构实现功能改性,但其材料表面极性固定、不具备动态可逆调控能力,仅能实现单次被动吸附,无法完成吸附饱和后的原位可控再生,材料单次使用后性能大幅衰减;更为关键的是,有机高分子壳层耐紫外老化、耐辐照性能极差,在光照、高温、真空等工况下极易发生光老化、链段断裂、基体降解等问题,不仅导致吸附功能快速失效,降解产生的高分子碎片还会混入稀土料液中,造成二次污染,严重制约高纯稀土、半导体、核工业等高纯净度场景的应用
[0031]与现有技术相比,本发明的有益效果是:(1)以镍锌铁氧体替代 Fe3O4作为所述磁性核,尖晶石结构中Ni2+与Zn2+的引入提高了晶格稳定性与抗酸溶能力,使所述光响应磁性复合粒子的耐酸性相较以Fe3O4为磁性核的粒子提升40倍以上,可在pH为0.5~2的稀土萃余液中长期使用,避免了磁性衰减与铁离子二次污染;同时所述中间层完全包覆磁性核,形成第二道耐酸屏障;(2)以多孔γ-Al2O3替代惰性SiO2作为所述中间层,在保持隔离防护功能的同时,其多孔结构为疏水性有机污染物提供额外的吸附容量,突破了现有核壳光响应粒子中间层不贡献吸附的局限;(3)所述光响应层以径向取向的WO3纳米线阵列形态原位生长于中间层表面,相较颗粒态堆积包覆,比表面积显著增大,光响应活性位点数量倍增,且所述WO3纳米线沿轴向为光生电子提供定向迁移通道,缩短了载流子迁移路径并减少复合损失,加快了光致变色响应速度;所述WO3纳米线的根部化学锚定于所述中间层,附着牢固,避免循环使用中脱落;(4)所述疏水化修饰层提供基线疏水性以提高无光照条件下的吸附容量,所述光响应层提供极性切换驱动力以实现紫外光触发脱附,两者叠加使表面水接触角的动态范围不小于40°,实现由疏水至亲水的大幅可逆切换;(5)紫外光触发的脱附为物理脱附过程,疏水性有机污染物的分子结构完整地脱附进入液相并可进一步富集回收,区别于光催化降解将有机物矿化损失;同时所述光响应磁性复合粒子仅对疏水性有机物具亲和力,对稀土离子基本不吸附,实现靶向去除有机污染物而保留稀土的选择性分离;(6)所述光响应磁性复合粒子的粒径为3~5μm,处于工业级高梯度磁分离可高效捕获的尺度区间,相较100nm以下的纳米粒子磁分离回收率高且不易团聚,相较0.3~0.8mm的吸附树脂比表面积提升数个数量级、传质路径大幅缩短;(7)由光控脱附替代蒸汽汽提与乙醇淋洗再生,无需配套蒸汽锅炉与溶剂回收塔,且无化学品消耗。
Smart Images

Figure FT_1 
Figure FT_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of magnetic composite materials technology, and in particular to a photoresponsive magnetic composite particle and its preparation method. Background Technology
[0002] Rare earth hydrometallurgy is the foundation of the high-end rare earth functional materials industry. Industrially, an extraction system is commonly constructed using acidic phosphorus extractants such as P204 and P507, combined with sulfonated kerosene as a diluent, to achieve the fractional separation and enrichment of rare earth elements. After extraction, a large amount of rare earth raffinate is continuously generated. This raffinate system is characterized by high acidity, the presence of valuable rare earth elements, and trace amounts of residual hydrophobic organic impurities. Its pH value is typically maintained in the strongly acidic range of 0.5–2. The dissolved and trace amounts of emulsified P204, P507, and sulfonated kerosene organic pollutants remaining in the liquid are key bottlenecks restricting the quality of rare earth purification and green industrial production. On the one hand, residual organic impurities can cause emulsification, scaling, and blockage in subsequent concentration, precipitation, and crystallization processes, significantly reducing the purity of high-purity rare earth products and causing the loss of valuable rare earth resources. On the other hand, direct discharge of raffinate containing large amounts of organic residues will cause serious water pollution and increase the cost of end-of-pipe environmental treatment. Therefore, the purification process of rare earth extraction residue is subject to stringent dual technical constraints: it must efficiently and effectively remove hydrophobic organic pollutants from the system to achieve deep purification of the feed solution, while retaining rare earth valent ions in the feed solution throughout the process to avoid resource depletion. This places extremely high industry standards on the acid resistance, adsorption selectivity, regeneration controllability, and cycle stability of adsorption and separation materials.
[0003] To address the challenge of purifying organic impurities in rare earth strong acid extraction residues, various adsorption materials and regeneration processes have been developed in this field, including traditional flocculation and demulsification, activated carbon adsorption, organic resin adsorption, and polymer-based magnetic adsorption materials. These technologies are gradually replacing traditional extensive treatment processes and have improved the purification effect of extraction residues to some extent. However, existing mainstream technologies all have inherent technical defects that cannot be overcome when adapting to the high acidity, high precision, recyclability, and continuous industrial conditions of rare earth processes. They are unable to simultaneously meet the core industrial requirements of corrosion resistance, high selectivity, low loss, gentle regeneration, and easy solid-liquid separation.
[0004] For example, Chinese patent CN91100655A discloses a magnetic particle-embedded macroporous polymer-based magnetic adsorption resin. This material uses an organic polymer as a matrix to embed magnetic powder, and relies on the polymer pores to achieve organic matter adsorption. The regeneration method depends on high-temperature steam stripping or repeated rinsing with organic solvents, which has the problems of extremely high regeneration energy consumption and large amount of reagent loss.
[0005] Another type of magnetic adsorption resin material uses organic polymers as the shell to achieve functional modification through polymer coating structure. However, the surface polarity of the material is fixed and it does not have the ability to dynamically and reversibly control it. It can only achieve passive adsorption once and cannot complete in-situ controllable regeneration after adsorption saturation. The performance of the material degrades significantly after a single use. More importantly, the organic polymer shell has extremely poor resistance to ultraviolet aging and radiation. Under conditions such as light, high temperature, and vacuum, it is prone to photoaging, chain segment breakage, and matrix degradation. This not only leads to rapid failure of adsorption function, but also causes polymer fragments generated by degradation to mix into rare earth liquid, causing secondary pollution. This seriously restricts the application of high-purity scenarios such as high-purity rare earth, semiconductor, and nuclear industries.
[0006] Furthermore, some existing magnetic adsorption materials specifically designed for acidic solutions have insufficient resistance to strong acid corrosion in their magnetic core components. Under long-term immersion in strongly acidic raffinate solutions with a pH of 0.5–2, the magnetic metal components are prone to acid dissolution and precipitation, directly causing the material's magnetic response performance to decay and its core-shell structure to become loose and collapse. This not only significantly shortens the material's cycle life, but the dissolved metal impurities also contaminate the high-purity rare earth finished product solution, reducing the product grade and resulting in extremely poor industrial stability and practicality.
[0007] In view of this, it is necessary to improve the magnetic particles in the existing technology to solve the above problems. Summary of the Invention
[0008] The purpose of this invention is to disclose a photoresponsive magnetic composite particle, which uses a nickel-zinc ferrite magnetic core to provide strong acid resistance, a porous γ-Al2O3 intermediate layer to provide both isolation and adsorption capacity, a WO3 nanowire array to improve photoresponse efficiency, and phenylsilane hydrophobic modification to synergize with the photochromic properties of the WO3, thereby achieving both a wide dynamic range of photocontrolled polarity switching and high adsorption capacity.
[0009] To achieve the above objectives, the present invention discloses a photoresponsive magnetic composite particle, the photoresponsive magnetic composite particle comprising a magnetic core, an intermediate layer coated on the surface of the magnetic core, a photoresponsive layer grown on the surface of the intermediate layer, and a hydrophobic modification layer grafted onto the surface of the photoresponsive layer;
[0010] The magnetic core is nickel-zinc ferrite, the intermediate layer is porous γ-Al2O3, the photoresponsive layer is a WO3 nanowire array grown radially along the surface of the intermediate layer, and the hydrophobic modification layer is phenylsilane.
[0011] The hydrophobic modification layer is a discontinuous molecular-level modification layer, and the photoresponsive active sites of the WO3 nanowire array are not blocked by the hydrophobic modification layer; the surface of the photoresponsive magnetic composite particles is hydrophobic under no light conditions and hydrophilic under ultraviolet light irradiation.
[0012] In some embodiments, based on a total mass of 100 parts of the photoresponsive magnetic composite particles, the magnetic core comprises 55 to 75 parts, the intermediate layer comprises 12 to 25 parts, the photoresponsive layer comprises 8 to 20 parts, and the hydrophobic modification layer comprises 0.5 to 4 parts.
[0013] In some embodiments, the particle size of the photoresponsive magnetic composite particles is 3–5 μm.
[0014] In some embodiments, the chemical formula of the nickel-zinc ferrite is Ni (1-x) Zn x Fe2O4, wherein x is 0.3 to 0.7; the particle size of the magnetic core is 1 to 3 μm, and the saturation magnetization of the magnetic core is not less than 40 emu / g.
[0015] In some embodiments, the thickness of the intermediate layer is 50–300 nm.
[0016] In some embodiments, the WO3 nanowires have a diameter of 20–100 nm and a length of 100–800 nm.
[0017] In some embodiments, the phenylsilane is one or more of phenyltrimethoxysilane, phenyltriethoxysilane, and diphenyldimethoxysilane.
[0018] In some embodiments, the water contact angle of the photoresponsive magnetic composite particles is not less than 120° under no-light conditions, and not greater than 80° under ultraviolet light irradiation at a wavelength of 365nm. The difference between the water contact angle under no-light conditions and under ultraviolet light irradiation is not less than 40°.
[0019] In some embodiments, after the photoresponsive magnetic composite particles are soaked in an acidic medium with a pH of 0.5 to 2 for 720 hours, the iron dissolution rate is not higher than 2%, and the saturation magnetization retention rate is not lower than 95%.
[0020] This invention also discloses a method for preparing photoresponsive magnetic composite particles, comprising the following steps:
[0021] S1: Preparation of magnetic cores: according to Ni (1-x) Zn x A mixed salt solution of nickel salt, zinc salt and ferrous salt was prepared by stoichiometric ratio of Fe2O4. The pH was adjusted under inert gas protection and a co-precipitation reaction was carried out at a certain temperature. The precipitate was magnetically separated, washed and dried, then calcined and pulverized to obtain the magnetic core.
[0022] S2: Coating the intermediate layer: The magnetic cores obtained in S1 are dispersed in a mixed solvent of ethanol and water, an aluminum source solution is added dropwise and a certain pH is maintained, and hydrolysis deposition is carried out; the resulting product is separated, washed, dried and then calcined to obtain particles coated with the intermediate layer;
[0023] S3: Growth of photoresponsive layer: The particles coated with the intermediate layer obtained in S2 are dispersed in a tungsten source precursor solution, the pH value is adjusted and a structure directing agent is added, and a hydrothermal reaction is carried out at a certain temperature to make the WO3 nanowire array grow in situ on the surface of the intermediate layer; the resulting product is magnetically separated, washed and then annealed.
[0024] S4: Hydrophobic grafting: After vacuum activation of the product obtained in S3, it is dispersed in an anhydrous organic solvent and phenylsilane is added for reflux grafting; the resulting product is subjected to magnetic separation, washing and solidification treatment to obtain the photoresponsive magnetic composite particles.
[0025] In some embodiments, in S1, the total metal ion concentration of the mixed salt solution is 0.5–1.5 mol / L; the mixed salt solution is adjusted to pH 10–12 under inert gas protection and co-precipitated at 60–90°C for 1–3 hours; the obtained precipitate is magnetically separated, washed, dried, calcined at 700–950°C for 2–4 hours, and then pulverized and graded to obtain the magnetic core.
[0026] In some embodiments, in step S2, an aluminum source solution is added dropwise to a mixed solvent while maintaining the pH at 7-9, and hydrolysis deposition is carried out at a temperature of 40-70°C for 2-6 hours; the resulting product is separated, washed, dried, and then calcined at a temperature of 500-650°C for 2-4 hours to obtain particles coated with the intermediate layer.
[0027] In some embodiments, the aluminum source solution is an aluminum isopropoxide solution or an aluminum nitrate solution.
[0028] In some embodiments, in step S3, the concentration of the tungsten source precursor solution is 0.02–0.15 mol / L, the pH is adjusted to 1–3 and a structure-directing agent is added, and the solution is subjected to hydrothermal reaction at 140–200°C for 6–24 h to allow the WO3 nanowire array to grow in situ on the surface of the intermediate layer; the resulting product is then magnetically separated, washed, and annealed at 300–450°C for 1–3 h.
[0029] In some embodiments, the tungsten source precursor solution is a sodium tungstate solution or a tungstic acid solution, and the structure directing agent is potassium sulfate or oxalic acid.
[0030] In some embodiments, in step S4, the product obtained in step S3 is vacuum activated at 110–130°C for 2–4 hours, then dispersed in an anhydrous organic solvent, and the phenylsilane is added, wherein the amount of phenylsilane is 1–6 wt% of the product mass. The product is then refluxed and grafted at 70–110°C for 4–12 hours. The resulting product is then magnetically separated, washed, and cured at 100–120°C for 1–3 hours to obtain the photoresponsive magnetic composite particles.
[0031] Compared with the prior art, the beneficial effects of the present invention are: (1) using nickel-zinc ferrite instead of Fe3O4 as the magnetic core, Ni in the spinel structure 2+ With Zn 2+The introduction of γ-Al2O3 improves the lattice stability and acid resistance, making the acid resistance of the photoresponsive magnetic composite particles more than 40 times higher than that of particles with Fe3O4 as the magnetic core. It can be used for a long time in rare earth leaching residue with pH 0.5 to 2, avoiding magnetic decay and secondary pollution by iron ions. At the same time, the intermediate layer completely covers the magnetic core, forming a second acid-resistant barrier. (2) Using porous γ-Al2O3 instead of inert SiO2 as the intermediate layer, while maintaining the isolation and protection function, its porous structure provides additional adsorption capacity for hydrophobic organic pollutants, thus improving the acid resistance of the photoresponsive magnetic composite particles. It breaks through the limitation that the intermediate layer of the existing core-shell photoresponsive particles does not contribute to adsorption; (3) The photoresponsive layer is grown in situ on the surface of the intermediate layer in the form of a radially oriented WO3 nanowire array. Compared with the particle stacking and coating, the specific surface area is significantly increased, the number of photoresponsive active sites is multiplied, and the WO3 nanowires provide a directional migration channel for photogenerated electrons along the axial direction, shortening the carrier migration path and reducing recombination loss, thus accelerating the photochromic response speed; the roots of the WO3 nanowires are chemically anchored to the intermediate layer, which is firmly attached and avoids falling off during recycling; (4) The The hydrophobic modification layer provides baseline hydrophobicity to improve adsorption capacity under no-light conditions, and the photoresponsive layer provides polarity switching driving force to achieve UV-triggered desorption. The superposition of the two makes the dynamic range of surface water contact angle not less than 40°, realizing a large-scale reversible switch from hydrophobic to hydrophilic; (5) UV-triggered desorption is a physical desorption process. The molecular structure of hydrophobic organic pollutants is completely desorbed into the liquid phase and can be further enriched and recovered, which is different from photocatalytic degradation that mineralizes and loses organic matter; at the same time, the photoresponsive magnetic composite particles only have affinity for hydrophobic organic matter, and have no affinity for other organic matter. Rare earth ions are basically not adsorbed, achieving selective separation of organic pollutants while retaining rare earths; (6) The particle size of the photoresponsive magnetic composite particles is 3-5 μm, which is within the scale range that can be efficiently captured by industrial-grade high gradient magnetic separation. Compared with nanoparticles below 100 nm, the magnetic separation recovery rate is high and they are not easy to agglomerate. Compared with adsorption resins of 0.3-0.8 mm, the specific surface area is increased by several orders of magnitude and the mass transfer path is greatly shortened; (7) Photo-controlled desorption replaces steam stripping and ethanol rinsing regeneration, eliminating the need for a matching steam boiler and solvent recovery tower, and eliminating chemical consumption. Attached Figure Description
[0032] Figure 1 This is a comparison diagram of the acid resistance stability of the photoresponsive magnetic composite particles shown in this invention;
[0033] Figure 2 This is a comparison diagram of the water contact angles of the photoresponsive magnetic composite particles shown in this invention. Detailed Implementation
[0034] The present invention will now be described in detail with reference to the embodiments shown in the accompanying drawings. However, it should be noted that these embodiments are not intended to limit the present invention. Any equivalent substitutions or replacements in function, method, or structure made by those skilled in the art based on these embodiments are within the scope of protection of the present invention.
[0035] This application discloses a photoresponsive magnetic composite particle, which includes a magnetic core, an intermediate layer coated on the surface of the magnetic core, a photoresponsive layer grown on the surface of the intermediate layer, and a hydrophobic modification layer grafted onto the surface of the photoresponsive layer.
[0036] The magnetic core is a nickel-zinc ferrite, and the chemical formula of the nickel-zinc ferrite is Ni. (1-x) Zn x The magnetic core is Fe2O4, where x is 0.3–0.7; the particle size of the magnetic core is 1–3 μm, and the saturation magnetization of the magnetic core is not less than 40 emu / g. The magnetic core is used to provide magnetic responsiveness to achieve magnetic separation and recovery, and also to provide resistance to strong acid corrosion.
[0037] The intermediate layer is a porous γ-Al₂O₃ that completely encapsulates the magnetic core. This serves two purposes: firstly, it isolates the magnetic core from the photoresponse layer and forms an acid-resistant barrier; secondly, its porous structure provides additional adsorption capacity. The thickness of the intermediate layer is 50–300 nm.
[0038] The photoresponsive layer is an array of WO3 nanowires grown radially along the surface of the intermediate layer, consisting of multiple WO3 nanowires. The diameter of the WO3 nanowires is 20–100 nm, and the length is 100–800 nm.
[0039] The hydrophobic modification layer is a phenylsilane, which is grafted onto the surface of the WO3 nanowires and the exposed surface of the intermediate layer via silicon-oxygen bonds, forming a discontinuous molecular-level modification layer. The phenylsilane is one or more of phenyltrimethoxysilane, phenyltriethoxysilane, and diphenyldimethoxysilane. The grafting density of the phenylsilane is 0.5–3.0 grafts / nm².
[0040] It should be noted that the amount of grafting of the hydrophobic modification layer must be controlled within the limit of improving hydrophobicity without blocking the photoresponsive active sites of the WO3 nanowire.
[0041] If the grafting amount is too low, the baseline hydrophobicity under no-light conditions will be insufficient, and the adsorption capacity will be low; if the grafting amount is too high, the photoresponsive active sites will be blocked, the polarity switching amplitude under ultraviolet light irradiation will decrease, and the two functions of hydrophobicity and photoresponsiveness will change from synergistic to antagonistic.
[0042] The hydrophobic modification layer is a discontinuous molecular-level modification layer, and the photoresponsive active sites of the WO3 nanowire array are not blocked by the hydrophobic modification layer; the surface of the photoresponsive magnetic composite particles is hydrophobic under no light conditions and hydrophilic under ultraviolet light irradiation.
[0043] Specifically, the photoresponsive magnetic composite particle comprises, based on a total mass of 100 parts, 55-75 parts of the magnetic core, 12-25 parts of the intermediate layer, 8-20 parts of the photoresponsive layer, and 0.5-4 parts of the hydrophobic modification layer.
[0044] The photoresponsive magnetic composite particles have a particle size of 3–5 μm. The selection of the particle size takes into account both specific surface area and magnetic separation and recovery: if the particle size is too small, it is difficult to efficiently capture the particles through high-gradient magnetic separation and they are prone to agglomeration; if the particle size is too large, the specific surface area decreases and the mass transfer path is prolonged.
[0045] The photoresponsive magnetic composite particles have a water contact angle of not less than 120° under no light conditions and a water contact angle of not more than 80° under ultraviolet light irradiation with a wavelength of 365nm. The difference between the water contact angle under no light conditions and under ultraviolet light irradiation is not less than 40°.
[0046] After being immersed in an acidic medium with a pH of 0.5–2 for 720 hours, the photoresponsive magnetic composite particles exhibit an iron dissolution rate of no more than 2% and a saturation magnetization retention rate of no less than 95%.
[0047] Working principle of photoresponsive magnetic composite particles: Under no-light conditions, the WO3 nanowires are in a W... 6+ The surface of the photoresponsive magnetic composite particles is strongly hydrophobic due to the low hydroxyl density in the fully oxidized state and the hydrophobic effect of the benzene ring groups in the hydrophobic modification layer. In this state, the photoresponsive magnetic composite particles exhibit strong adsorption affinity for hydrophobic organic pollutants such as P204 (di(2-ethylhexyl)phosphoric acid), P507 (2-ethylhexylphosphonic acid mono-2-ethylhexyl ester), and sulfonated kerosene. These hydrophobic organic pollutants accumulate on the surface of the photoresponsive magnetic composite particles and within the porous structure of the intermediate layer through hydrophobic interactions and π-π interactions.
[0048] Under ultraviolet light irradiation at a wavelength of 365 nm, the WO3 nanowires absorb photons to generate electron-hole pairs, and the photogenerated electrons will... 6+ Restore to W 5+ During photochromism, protonation and hydration occur on the surface, significantly increasing the hydroxyl group density and surface free energy, thus changing the hydrophobic nature to a hydrophilic one. The affinity of the hydrophobic organic pollutants, which were originally bound by hydrophobic interactions, drops sharply, triggering desorption into the liquid phase.
[0049] After the ultraviolet light is removed, W 5+ It is re-oxidized to W under the action of dissolved oxygen. 6+ The surface of the photoresponsive magnetic composite particles is restored to a hydrophobic state and regains its adsorption capacity, thereby enabling recycling.
[0050] It should be emphasized that the above-mentioned ultraviolet light-triggered desorption is physical desorption, and the molecular structure of the hydrophobic organic pollutants is not destroyed, so they can be further enriched and recovered; at the same time, rare earth ions do not participate in the above-mentioned adsorption and desorption process because they are not hydrophobic, and remain intact in the feed solution.
[0051] This application also discloses a method for preparing photoresponsive magnetic composite particles, comprising the following steps:
[0052] S1: Preparation of magnetic cores: according to Ni (1-x) Zn x A mixed salt solution of nickel salt, zinc salt and ferrous salt was prepared by stoichiometric ratio of Fe2O4. The pH was adjusted under inert gas protection and a co-precipitation reaction was carried out at a certain temperature. The precipitate was magnetically separated, washed and dried, then calcined and pulverized to obtain the magnetic core.
[0053] S2: Coating the intermediate layer: The magnetic cores obtained in S1 are dispersed in a mixed solvent of ethanol and water with a solid content of 2-10 wt%. An aluminum source solution is added dropwise while maintaining a certain pH to carry out hydrolysis and deposition. The resulting product is separated, washed, dried, and then calcined to obtain particles coated with the intermediate layer.
[0054] S3: Growth of photoresponsive layer: The particles coated with the intermediate layer obtained in S2 are dispersed in a tungsten source precursor solution, the pH value is adjusted and a structure directing agent is added, and a hydrothermal reaction is carried out at a certain temperature to make the WO3 nanowire array grow in situ on the surface of the intermediate layer; the resulting product is magnetically separated, washed and then annealed.
[0055] S4: Hydrophobic grafting: After vacuum activation of the product obtained in S3, it is dispersed in an anhydrous organic solvent and phenylsilane is added for reflux grafting; the resulting product is subjected to magnetic separation, washing and solidification treatment to obtain the photoresponsive magnetic composite particles.
[0056] In step S1, the total metal ion concentration of the mixed salt solution is 0.5–1.5 mol / L; the mixed salt solution is stirred under inert gas protection, the pH is adjusted to 10–12, and co-precipitation is carried out at 60–90°C for 1–3 hours; the precipitate is magnetically separated, washed with deionized water until neutral, dried at 80–105°C, and then calcined at 700–950°C for 2–4 hours, and then pulverized and graded to obtain the magnetic core of 1–3 μm.
[0057] In step S2, an aluminum source solution is added dropwise to a mixed solvent while maintaining the pH at 7–9. Hydrolysis deposition is carried out at 40–70°C for 2–6 hours. The resulting product is separated, washed, dried at 80–105°C, and then calcined at 500–650°C for 2–4 hours to transform alumina into a γ-crystalline form, forming an intermediate layer with a thickness of 50–300 nm, thus obtaining particles coated with the intermediate layer.
[0058] The aluminum source solution is aluminum isopropoxide solution or aluminum nitrate solution.
[0059] In step S3, the concentration of the tungsten source precursor solution is 0.02–0.15 mol / L. The pH is adjusted to 1–3 and a structure-directing agent is added. The solution is subjected to hydrothermal reaction at 140–200 °C for 6–24 h to allow the WO3 nanowire array to grow in situ on the surface of the intermediate layer. The resulting product is then magnetically separated, washed, and annealed at 300–450 °C for 1–3 h.
[0060] The tungsten source precursor solution is a sodium tungstate solution or a tungstic acid solution, and the structure directing agent is potassium sulfate or oxalic acid.
[0061] In step S4, the product obtained in step S3 is vacuum activated at 110–130°C for 2–4 h, then dispersed in an anhydrous organic solvent, and the phenylsilane is added. The amount of phenylsilane is 1–6 wt% of the product mass. The product is then refluxed and grafted at 70–110°C for 4–12 h. After magnetic separation and washing, the obtained product is cured at 100–120°C for 1–3 h to obtain the photoresponsive magnetic composite particles.
[0062] Example 1
[0063] The photoresponsive magnetic composite particles were prepared according to the above method, with the specific process conditions as follows:
[0064] S1: Press Ni 0.5 Zn 0.5 A mixed salt solution was prepared using Fe2O4 at a stoichiometric ratio, with a total metal ion concentration of 1.0 mol / L. Under nitrogen protection, the mixture was stirred at 450 r / min, and the pH was adjusted to 11 with sodium hydroxide. The mixture was then co-precipitated at 80 °C for 2 h. The precipitate was magnetically separated, washed with deionized water until neutral, dried at 100 °C, and then calcined at 850 °C for 3 h. The magnetic cores with a particle size of 1 μm were obtained by air jet milling and classification.
[0065] S2: The magnetic core is dispersed in a mixed solvent of ethanol and water with a solid content of 5 wt%; aluminum isopropoxide solution is added dropwise while maintaining the pH at 8, and hydrolysis deposition is carried out at 60°C for 4 h; the product is separated, washed, dried at 100°C, and then calcined at 580°C for 3 h to obtain the intermediate layer with a thickness of 150 nm.
[0066] S3: The above particles were dispersed in a sodium tungstate solution with a concentration of 0.08 mol / L, the pH was adjusted to 2 with hydrochloric acid, potassium sulfate was added as a structure directing agent, and the mixture was hydrothermally reacted at 180℃ for 12 h. The product was magnetically separated, washed, and then annealed at 400℃ for 2 h to obtain the WO3 nanowire array with a diameter of 50 nm and a length of 400 nm.
[0067] S4: The above particles were activated under vacuum at 120°C for 3 hours, dispersed in anhydrous toluene, and phenyltrimethoxysilane was added at an amount of 3 wt% of the particle mass. The particles were then refluxed at 90°C for 8 hours under nitrogen protection. After magnetic separation and washing with anhydrous ethanol, the product was cured at 110°C for 2 hours.
[0068] The obtained photoresponsive magnetic composite particles have a particle size of 3.28 μm and a saturation magnetization of 48 emu / g.
[0069] Example 2
[0070] The photoresponsive magnetic composite particles were prepared according to the above method, with the specific process conditions as follows:
[0071] S1: Press Ni 0.7 Zn 0.3 A mixed salt solution was prepared using Fe2O4 at a stoichiometric ratio, with a total metal ion concentration of 0.5 mol / L. Under nitrogen protection, the mixture was stirred at 450 r / min, and the pH was adjusted to 10 with sodium hydroxide. The mixture was then co-precipitated at 90 °C for 1 h. The precipitate was magnetically separated, washed with deionized water until neutral, dried at 100 °C, and then calcined at 700 °C for 4 h. The magnetic cores with a particle size of 2 μm were obtained by air jet milling and classification.
[0072] S2: The magnetic core is dispersed in a mixed solvent of ethanol and water with a solid content of 5 wt%; aluminum isopropoxide solution is added dropwise while maintaining pH at 9, and hydrolysis deposition is carried out at 70°C for 2 h; the product is separated, washed, dried at 100°C, and then calcined at 600°C for 2 h to obtain an intermediate layer with a thickness of 80 nm.
[0073] S3: The above particles were dispersed in a sodium tungstate solution with a concentration of 0.15 mol / L, the pH was adjusted to 1 with hydrochloric acid, and potassium sulfate was added as a structure directing agent; the reaction was carried out hydrothermally at 200℃ for 24 h; after magnetic separation and washing, the product was annealed at 450℃ for 3 h to obtain the WO3 nanowire array with a diameter of 45 nm and a length of 380 nm.
[0074] S4: The above particles were activated in vacuum at 130℃ for 2 hours, dispersed in anhydrous toluene, and phenyltrimethoxysilane was added at an amount of 1.5 wt% of the particle mass; the grafting was carried out under reflux at 70℃ for 12 hours under nitrogen protection; the product was then magnetically separated, washed with anhydrous ethanol, and cured at 100℃ for 3 hours.
[0075] The obtained photoresponsive magnetic composite particles have a particle size of 4.1 μm and a saturation magnetization of 56 emu / g.
[0076] Example 3
[0077] The photoresponsive magnetic composite particles were prepared according to the above method, with the specific process conditions as follows:
[0078] S1: Press Ni 0.5 Zn 0.5 A mixed salt solution was prepared using Fe2O4 at a stoichiometric ratio, with a total metal ion concentration of 1.5 mol / L. Under nitrogen protection, the mixture was stirred at 450 r / min, and the pH was adjusted to 12 with sodium hydroxide. The mixture was then co-precipitated at 60 °C for 3 h. The precipitate was magnetically separated, washed until neutral, dried at 100 °C, and then calcined at 950 °C for 2 h. The magnetic cores with a particle size of 2.8 μm were obtained by air jet milling and classification.
[0079] S2: The magnetic core is dispersed in a mixed solvent of ethanol and water with a solid content of 5 wt%; aluminum isopropoxide solution is added dropwise while maintaining the pH at 7, and hydrolysis deposition is carried out at 40°C for 6 h; the product is separated, washed, dried at 100°C, and then calcined at 500°C for 4 h to obtain the intermediate layer with a thickness of 130 nm.
[0080] S3: The above particles were dispersed in a sodium tungstate solution with a concentration of 0.02 mol / L, the pH was adjusted to 1 with hydrochloric acid, and potassium sulfate was added as a structure directing agent; the reaction was carried out hydrothermally at 160℃ for 20 h; after magnetic separation and washing, the product was annealed at 400℃ for 2 h to obtain the WO3 nanowire array with a diameter of 30 nm and a length of 700 nm.
[0081] S4: The above particles were activated in vacuum at 120℃ for 3h, dispersed in anhydrous toluene, and phenyltriethoxysilane was added at an amount of 5 wt% of the particle mass; the grafting was carried out under reflux at 90℃ for 8h under nitrogen protection; the product was then magnetically separated, washed with anhydrous ethanol, and cured at 110℃ for 2h.
[0082] The obtained photoresponsive magnetic composite particles have a particle size of approximately 4.93 μm and a saturation magnetization of approximately 65 emu / g.
[0083] Comparative Example 1
[0084] This comparative example is used to verify the strong acid resistance of the magnetic core. Fe3O4 is used instead of the nickel-zinc ferrite as the magnetic core, and the remaining steps are the same as in Example 1. The specific process conditions are as follows:
[0085] S1: According to Fe 2+ :Fe 3+ A mixed salt solution of ferrous sulfate and ferric sulfate was prepared at a molar ratio of 1:2, with a total metal ion concentration of 1.0 mol / L. Under nitrogen protection, the mixture was stirred at 450 r / min, and the pH was adjusted to 11 with sodium hydroxide. The mixture was then co-precipitated at 80 °C for 2 h. The precipitate was magnetically separated, washed until neutral, and dried at 100 °C to obtain Fe3O4 magnetic nuclei with a particle size of 2 μm.
[0086] S2-S4: Completely the same as in Example 1, obtaining Fe3O4@γ-Al2O3@WO3 nanowire array@phenylsilane particles.
[0087] Comparative Example 2
[0088] This comparative example is used to verify the adsorption and compatibilization function of the intermediate layer. SiO2 is used instead of porous γ-Al2O3 as the intermediate layer, and the remaining steps are the same as in the example. The specific process conditions are as follows:
[0089] S1: Same as in Example 1, Ni is obtained. 0.5 Zn 0.5 Fe2O4 magnetic core.
[0090] S2: The magnetic core is dispersed in a mixed solvent of ethanol and water with a solid content of 5 wt%; tetraethyl orthosilicate is added dropwise while maintaining the pH at 8-9, and hydrolysis deposition is carried out at 60°C for 4 h; the product is separated, washed, and dried at 100°C to obtain a SiO2 intermediate layer with a thickness of 150 nm.
[0091] S3-S4: Same as in Example 1, grow WO3 nanowire arrays and graft 3wt% phenyltrimethoxysilane to obtain Ni 0.5 Zn 0.5 Fe2O4@SiO2@WO3 nanowire array@phenylsilane particles.
[0092] Comparative Example 3
[0093] The hydrophobic grafting in step S4 is omitted, and the remaining steps and process conditions are the same as in Example 1, resulting in particles without the hydrophobic modification layer.
[0094] Comparative Example 4
[0095] The photoresponse layer growth in S3 is omitted, and the particles obtained in S2 are directly subjected to hydrophobic grafting in S4. The remaining process conditions are the same as in Example 1, resulting in particles without the aforementioned photoresponse layer.
[0096] Comparative Example 5
[0097] In S3, the in-situ orientation growth of the WO3 nanowire array is replaced by granular WO3 coating, that is, pre-made WO3 nanoparticles are coated on the surface of the intermediate layer by physical deposition. The remaining steps and process conditions are the same as in Example 1.
[0098] Performance testing
[0099] 1. Acid resistance stability test:
[0100] 1.0 g of particles were placed in 100 mL of sulfuric acid medium with pH 1.0 and allowed to stand for 720 h at 25 °C. The supernatant was periodically collected and the iron ion concentration was determined by inductively coupled plasma optical emission spectroscopy (ICP-OES) to calculate the iron dissolution rate. The saturation magnetization was measured by a vibrating sample magnetometer (VSM) before and after soaking and the retention rate was calculated.
[0101] 2. Water contact angle test:
[0102] The water contact angle of the particle tablet surface was determined using the droplet method on a contact angle measuring instrument.
[0103] 3. Adsorption and desorption properties:
[0104] The saturated adsorption capacity for P204 was determined by batch method; the saturated adsorption particles were irradiated with 365 nm ultraviolet light and the photocontrolled desorption rate (desorption amount / adsorption amount) was measured; the adsorption amount of rare earth ions was determined by ICP-OES, and this application uses La... 3+ The adsorption capacity is represented by the capacity retention rate, which is determined after the particles are cycled 100 times under the "dark adsorption-ultraviolet desorption" condition.
[0105] Table 1 Acid resistance stability test
[0106] sample Iron dissolution rate Saturation magnetization retention rate Example 1 0.8% 98% Example 2 1.1% 97% Example 3 0.9% 98% Comparative Example 1 42% 55%
[0107] Depend on Figure 1 As shown in Table 1, in Examples 1 to 3, the nickel-zinc ferrite was used as the magnetic core, and its iron dissolution rate was significantly lower than that of Comparative Example 1, which used Fe3O4 as the magnetic core. The acid resistance was improved by more than 40 times, and the saturation magnetization retention rate was also improved from 55% in Comparative Example 1 to 97-98%.
[0108] This is because nickel-zinc ferrite Ni (1-x) Zn x Fe₂O₄ has a spinel structure, Ni 2+With Zn 2+ By entering the lattice and substituting some Fe sites, the lattice pairing with H is significantly improved. + The erosion resistance ensures that the magnetic core is almost undissolved in strongly acidic systems with a pH of 0.5–2; simultaneously, the intermediate layer completely encapsulates the magnetic core, forming a second acid-resistant barrier. Comparative Example 1 uses an Fe3O4 magnetic core, whose inverse spinel structure contains Fe... 2+ Located in the tetrahedral void, it is extremely easy to be H + The substitution and dissolution result in a large influx of iron ions into the feed solution, causing irreversible degradation of magnetic properties. This demonstrates that replacing Fe3O4 with the nickel-zinc ferrite is key to the long-term serviceability of this invention in strong acid rare earth feed solutions, overcoming the problem of easy dissolution of magnetic components under strong acid conditions in existing technologies.
[0109] Table 2 Water Contact Angle Test
[0110] sample Water contact angle in the absence of light Water contact angle under 365nm ultraviolet light irradiation Example 1 128° 72° Example 2 124° 78° Example 3 130° 70° Comparative Example 3 95° 82° Comparative Example 4 120° 119° Comparative Example 5 122° 88°
[0111] Depend on Figure 2 As shown in Table 2, the water contact angles in Examples 1-3 differ by no less than 40° under both light-free and UV-irradiated conditions, achieving a significant reversible switch from hydrophobic to hydrophilic. Comparative Example 3, lacking the hydrophobic modification layer, exhibits insufficient baseline hydrophobicity under light-free conditions; Comparative Example 4, lacking the photoresponse layer, completely lacks polarity switching capability; Comparative Example 5, although containing a hydrophobic modification layer, still falls below the threshold of this invention due to the granular packing of WO3, resulting in decreased specific surface area and photogenerated electron migration efficiency. The dynamic range of all three examples is significantly lower than that of the Examples, demonstrating a synergistic effect between the hydrophobic modification layer and the photoresponse layer. The hydrophobic modification layer provides baseline hydrophobicity, while the photoresponse layer provides the driving force for polarity switching. The combination of these two elements ensures that the difference in water contact angle between light-free and light-irradiated conditions is no less than 40°, and the WO3 nanowire array morphology is essential for achieving a large dynamic range.
[0112] Table 3 Adsorption and desorption performance tests
[0113] sample P204 saturated adsorption capacity (mg / g) Light-controlled desorption rate Rare earth ion adsorption capacity (mg / g) Capacity retention after 100 cycles Example 1 86 96% 0.2 95% Comparative Example 2 48 95% 0.2 94% Comparative Example 3 38 90% 0.1 88%
[0114] As shown in Table 3, the saturated adsorption capacity of P2O4 in Example 1 is significantly higher than that in Comparative Example 2, which uses SiO2 as the intermediate layer. This demonstrates that the porous γ-Al2O3 intermediate layer provides additional adsorption capacity due to its high specific surface area, overcoming the limitation that the intermediate layer of existing core-shell photoresponsive particles does not contribute to adsorption. Meanwhile, the adsorption capacity of rare earth ions in Example 1 is close to zero, demonstrating that the photoresponsive magnetic composite particles only have affinity for hydrophobic organic matter and possess targeting selectivity.
[0115] Comparative Example 3, lacking the hydrophobic modification layer, exhibited insufficient baseline hydrophobicity under no-light conditions. P204 primarily relied on the weak interfacial interaction of the WO3 photoresponsive layer for adsorption, resulting in a sharp drop in saturated adsorption capacity to approximately 38 mg / g. Although polarity switching and desorption of most adsorbed pollutants occurred under UV irradiation, the low total adsorption capacity further illustrates the crucial role of the hydrophobic modification layer in adsorption capacity. After 100 cycles of "dark-state adsorption-UV desorption," Example 1 maintained a capacity retention rate of 95%, demonstrating that the root chemical anchoring of the WO3 nanowires ensured the photoresponsive layer remained firmly attached during cyclic use, allowing for long-term stable use of the photoresponsive magnetic composite particles.
[0116] The detailed descriptions listed above are merely specific descriptions of feasible embodiments of the present invention, and are not intended to limit the scope of protection of the present invention. All equivalent embodiments or modifications made without departing from the spirit of the present invention should be included within the scope of protection of the present invention.
[0117] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A photoresponsive magnetic composite particle, characterized in that, The photoresponsive magnetic composite particle includes a magnetic core, an intermediate layer coated on the surface of the magnetic core, a photoresponsive layer grown on the surface of the intermediate layer, and a hydrophobic modification layer grafted onto the surface of the photoresponsive layer. The magnetic core is nickel-zinc ferrite, the intermediate layer is porous γ-Al2O3, the photoresponsive layer is a WO3 nanowire array grown radially along the surface of the intermediate layer, and the hydrophobic modification layer is phenylsilane. The hydrophobic modification layer is a discontinuous molecular-level modification layer, and the photoresponsive active sites of the WO3 nanowire array are not blocked by the hydrophobic modification layer; the surface of the photoresponsive magnetic composite particles is hydrophobic under no light conditions and hydrophilic under ultraviolet light irradiation.
2. The photoresponsive magnetic composite particle according to claim 1, characterized in that, Based on a total mass of 100 parts for the photoresponsive magnetic composite particles, the magnetic core comprises 55-75 parts, the intermediate layer comprises 12-25 parts, the photoresponsive layer comprises 8-20 parts, and the hydrophobic modification layer comprises 0.5-4 parts.
3. The photoresponsive magnetic composite particle according to claim 2, characterized in that, The particle size of the photoresponsive magnetic composite particles is 3–5 μm.
4. The photoresponsive magnetic composite particle according to claim 1, characterized in that, The chemical formula of the nickel-zinc ferrite is Ni (1-x) Zn x Fe2O4, wherein x is 0.3 to 0.7; the particle size of the magnetic core is 1 to 3 μm, and the saturation magnetization of the magnetic core is not less than 40 emu / g.
5. The photoresponsive magnetic composite particle according to claim 1, characterized in that, The thickness of the intermediate layer is 50–300 nm.
6. The photoresponsive magnetic composite particle according to claim 1, characterized in that, The WO3 nanowires have a diameter of 20–100 nm and a length of 100–800 nm.
7. The photoresponsive magnetic composite particle according to claim 1, characterized in that, The phenylsilane is one or more of phenyltrimethoxysilane, phenyltriethoxysilane, and diphenyldimethoxysilane.
8. The photoresponsive magnetic composite particle according to claim 1, characterized in that, The photoresponsive magnetic composite particles have a water contact angle of not less than 120° under no light conditions and a water contact angle of not more than 80° under ultraviolet light irradiation with a wavelength of 365nm. The difference between the water contact angle under no light conditions and under ultraviolet light irradiation is not less than 40°.
9. The photoresponsive magnetic composite particle according to claim 1, characterized in that, After being immersed in an acidic medium with a pH of 0.5–2 for 720 hours, the photoresponsive magnetic composite particles exhibit an iron dissolution rate of no more than 2% and a saturation magnetization retention rate of no less than 95%.
10. A method for preparing photoresponsive magnetic composite particles as described in any one of claims 1 to 9, characterized in that, Includes the following steps: S1: Preparation of magnetic cores: according to Ni (1-x) Zn x A mixed salt solution of nickel salt, zinc salt and ferrous salt was prepared by stoichiometric ratio of Fe2O4. The pH was adjusted under inert gas protection and a co-precipitation reaction was carried out at a certain temperature. The precipitate was magnetically separated, washed and dried, then calcined and pulverized to obtain the magnetic core. S2: Coating the intermediate layer: The magnetic cores obtained in S1 are dispersed in a mixed solvent of ethanol and water, an aluminum source solution is added dropwise and a certain pH is maintained, and hydrolysis deposition is carried out; the resulting product is separated, washed, dried and then calcined to obtain particles coated with the intermediate layer; S3: Growth of photoresponsive layer: The particles coated with the intermediate layer obtained in S2 are dispersed in a tungsten source precursor solution, the pH value is adjusted and a structure directing agent is added, and a hydrothermal reaction is carried out at a certain temperature to make the WO3 nanowire array grow in situ on the surface of the intermediate layer; the resulting product is magnetically separated, washed and then annealed. S4: Hydrophobic grafting: After vacuum activation of the product obtained in S3, it is dispersed in an anhydrous organic solvent and phenylsilane is added for reflux grafting; the resulting product is subjected to magnetic separation, washing and solidification treatment to obtain the photoresponsive magnetic composite particles.
11. The method for preparing photoresponsive magnetic composite particles according to claim 10, characterized in that, In S1, the total metal ion concentration of the mixed salt solution is 0.5–1.5 mol / L; the mixed salt solution is adjusted to pH 10–12 under inert gas protection and co-precipitated at 60–90°C for 1–3 hours; the precipitate is magnetically separated, washed, dried, calcined at 700–950°C for 2–4 hours, and then pulverized and graded to obtain the magnetic core.
12. The method for preparing photoresponsive magnetic composite particles according to claim 10, characterized in that, In step S2, an aluminum source solution is added dropwise to a mixed solvent while maintaining the pH at 7-9, and hydrolysis deposition is carried out at 40-70°C for 2-6 hours. The resulting product is then separated, washed, and dried, and calcined at 500-650°C for 2-4 hours to obtain particles coated with the intermediate layer.
13. The method for preparing photoresponsive magnetic composite particles according to claim 12, characterized in that, The aluminum source solution is aluminum isopropoxide solution or aluminum nitrate solution.
14. The method for preparing photoresponsive magnetic composite particles according to claim 10, characterized in that, In step S3, the concentration of the tungsten source precursor solution is 0.02–0.15 mol / L. The pH is adjusted to 1–3 and a structure-directing agent is added. The solution is subjected to hydrothermal reaction at 140–200 °C for 6–24 h to allow the WO3 nanowire array to grow in situ on the surface of the intermediate layer. The resulting product is then magnetically separated, washed, and annealed at 300–450 °C for 1–3 h.
15. The method for preparing photoresponsive magnetic composite particles according to claim 14, characterized in that, The tungsten source precursor solution is a sodium tungstate solution or a tungstic acid solution, and the structure directing agent is potassium sulfate or oxalic acid.
16. The method for preparing photoresponsive magnetic composite particles according to claim 10, characterized in that, In step S4, the product obtained in step S3 is vacuum activated at 110–130°C for 2–4 h, then dispersed in an anhydrous organic solvent, and the phenylsilane is added. The amount of phenylsilane is 1–6 wt% of the product mass. The product is then refluxed and grafted at 70–110°C for 4–12 h. After magnetic separation and washing, the obtained product is cured at 100–120°C for 1–3 h to obtain the photoresponsive magnetic composite particles.
Citation Information
Patent Citations
Preparation of magnetic macroporous ion-exchange resin for adsorption
CN1036526C